1988
DOI: 10.1080/15287398809531118
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transport, thiol status, and hepatotoxicity followingN‐nitrosodimethylamine exposure in mice

Abstract: The hepatotoxicant N-nitrosodimethylamine (NDMA) is presumed to exert toxicity through reactive metabolites. NDMA is similar in this respect to numerous other hepatotoxicants, for which hepatotoxicity is also associated with a rapid depletion of soluble and/or protein thiols, and an inhibition of calcium transport systems. We examined the hypothesis that hepatotoxicity for NDMA is preceded by thiol depletion and/or inhibition of calcium transport in isolated liver subcellular fractions. Centrizonal liver necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…N -Nitrosodimethylamine (NDMA), the simplest and most widely occurring nitrosamine, has been shown to be an acute hepatotoxin and potent carcinogen in a variety of animal species and humans ( ). It is generally believed that the metabolic activation of NDMA to reactive intermediates by cytochrome P450 2E1 is required for it to exert its carcinogenic and hepatotoxic effects ( , ).…”
Section: Introductionmentioning
confidence: 99%
“…N -Nitrosodimethylamine (NDMA), the simplest and most widely occurring nitrosamine, has been shown to be an acute hepatotoxin and potent carcinogen in a variety of animal species and humans ( ). It is generally believed that the metabolic activation of NDMA to reactive intermediates by cytochrome P450 2E1 is required for it to exert its carcinogenic and hepatotoxic effects ( , ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of membrane protein sulfhydryl groups on permeability is widely known. In fact, there is a large body of evidence in favor of thiol group participation in the control of mitochondrial Ca 2+ transport, for example, Chávez and Holguín (), Reitman et al (), and Moore et al (). In previous work, we demonstrated that the binding of Hg 2+ to proteins with molecular weights between the ranges of 20–30 kDa induces the opening of a non‐specific pore (Chávez and Holguín, ).…”
Section: Resultsmentioning
confidence: 99%
“…NDMA has been shown to be an acute hepatotoxin and a potent carcinogen in many animal species and also potentially in humans [16,17]. In experiments with human liver microsomes, it has been demonstrated that cytochrome P450 2EI is the major enzyme responsible for the oxidative demethylation of NDMA at low substrate concentrations [18].…”
Section: Discussionmentioning
confidence: 99%